ANALISIS PRINSIP KESANTUNAN BERBAHASA PADA CERPEN “PAK ADIL MENCARI KEADILAN” KARYA GOL A GONG - Indah Lestari (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
The politeness of the language becomes important in communicating. Politeness in communication is a must because it reflects someone being polite and polite in speaking. The politeness of language must be taught from childhood. One application is learning in schools. Short story as one of the subject matter which includes conversations that must also include the principle of politeness in language. The problem that will be discussed in this research is "How to use politeness in the short story titled Mr. Adil Looking for Justice by Gol A Gong?". This study aims to describe the use of politeness in language in a short story entitled Mr. Adil Seeking Justice by Gol A Gong. The method in this research uses descriptive method. The data used in this study is dialogue that contains politeness in language. The data collection techniques in this study used reading, note taking, library, and analysis techniques. Based on the results of the study concluded that in the short story titled Mr. Adil Seeking Justice meets the principles of politeness in language, including maxim of wisdom, maxim of simplicity, maxim of compatibility, maxim of generosity, and maxim of sympathy.